Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
x = 1
Step-by-step explanation:
5x - (4x - 1) = 2
Let's get rid of the parenthesis
Multiply whatever is in the parenthesis by -1 since there is a minus sign before it
5x - 4x + 1 = 2
Move common terms to one side, so subtract 1 from both sides
5x - 4x + 1 = 2
- 1 - 1
5x - 4x = 1
Subtract the 5x by 4x
x = 1
Answer:
x = 1
Step-by-step explanation:
5x - (4x - 1) = 2
5x - 4x + 1 = 2 {Distribute property (-1) is distributed with 4x and (-1)}
Combine like terms
x + 1 = 2
Subtract 1 from both sides
x = 2 - 1
x = 1
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.